Tech for Kids untuk Memperkenalkan Siswa Mengenai Tahapan Merakit Purwarupa dalam Proses Desain Rekayasa - Deny Nusyirwan; Eko Prayetno; Sapta Nugraha; Harits Aditya Nugraha; Lilis Agustina Sinaga; Allysia Shafira; Muhammad Abyan Fadillah (Universitas Mathla'ul Anwar Banten, 2021)
TECH FOR KIDS FOR INTRODUCING THE STUDENTS ABOUT THE STAGE OF PROTOTYPE ASSEMBLING IN ENGINEERING DESIGN PROCESS. Individuals must be able to adapt effectively to changing situations rather than rely solely on rote learning procedures. Therefore, the call for 21st century skills is a call for deeper learning - helping students to develop transferable knowledge that can be applied to new situations and problems. Virtual prototypes are perhaps the greatest benefit that comes from using computer-aided designs. Virtual prototypes allow high-quality design. Adjust spare parts with proper clearance and check for parts glitches before spending on material shopping. Designers can also "dress" the product in multiple layers of materials and colors to see what your product will look like. And by the time the designer gets to the point where it is going to create a physical prototype, the Designer has a good idea of how the product will operate and what it will look like. Furthermore, if there is a change in the physical prototype, the changes will be far less than if the virtual model was never created. With this background, Tech for Kids training was held to introduce students to the stages of assembling prototypes in the engineering design process.